Acoustic emission monitoring of multiaxial ultimate elastic wall stress tests of glass fibre-reinforced epoxy composite pipes - Mohd Shukry, Abdul Majid (Taylor & Francis, 2014)
Link to publisher's homepage at http://www.tandfonline.com